2003
DOI: 10.1046/j.1365-2672.2003.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trehalose on survival of Bradyrhizobium japonicum during desiccation

Abstract: Aims: A major reason for the ineffectiveness of legume inoculants in the field is the rapid death of rhizobia because of desiccation. The major purpose of this study was to identify conditions under which a,a-trehalose would improve survival of Bradyrhizobium japonicum during desiccation. Methods and Results: Trehalose was added to cultures just prior to desiccation or was supplied to bacteria during the 6-day growth period. A wide variety of trehalose concentrations was tested. Trehalose added to cultures at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 29 publications
12
74
2
3
Order By: Relevance
“…Similarly, Streeter (2003) reported that cell numbers of B. japonicum USDA110 were significantly higher in cultures with trehalose added to the basal medium compared with cultures with added maltose after three to four days of growth. Although Streeter (2003) The accumulation of intracellular trehalose by B. japonicum USDA110 was increased by supplying trehalose in the growth medium.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Similarly, Streeter (2003) reported that cell numbers of B. japonicum USDA110 were significantly higher in cultures with trehalose added to the basal medium compared with cultures with added maltose after three to four days of growth. Although Streeter (2003) The accumulation of intracellular trehalose by B. japonicum USDA110 was increased by supplying trehalose in the growth medium.…”
Section: Discussionmentioning
confidence: 83%
“…Adding 3 mM trehalose to the growth medium of B. japonicum USDA110 increased intracellular trehalose accumulation by three-fold, which in turn resulted in a 294% increase in survival of cells after 24 hours of being air-dried on soybean seed (Streeter, 2003). Streeter (2007) reported that adding sodium chloride and trehalose to the growth medium of USDA110 cultures resulted in a larger increase in trehalose accumulation than using trehalose alone.…”
Section: Role Of Trehalose In Desiccation Tolerancementioning
confidence: 99%
See 3 more Smart Citations